2017
DOI: 10.1103/physreve.95.062310
|View full text |Cite
|
Sign up to set email alerts
|

Spectral partitioning in equitable graphs

Abstract: Graph partitioning problems emerge in a wide variety of complex systems, ranging from biology to finance, but can be rigorously analyzed and solved only for a few graph ensembles. Here, an ensemble of equitable graphs, i.e. random graphs with a block-regular structure, is studied, for which analytical results can be obtained. In particular, the spectral density of this ensemble is computed exactly for a modular and bipartite structure. Kesten-McKay's law for random regular graphs is found analytically to apply… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Since the rank of X is r, it follows that the nullity of X * is n − r, so there are n − r independent vectors w for which X * w = 0. Now, note that picking v 1 = w, v 2 = 0, and λ = ±i √ d 1 − 1, we satisfy equations (4) and (5). Thus, ±i √ d 1 − 1 are eigenvalues of B, both with multiplicity n − r. The remaining 4r eigenvalues of B determined by A come from nonzero eigenvalues of A.…”
Section: Connecting the Spectra Of A And Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the rank of X is r, it follows that the nullity of X * is n − r, so there are n − r independent vectors w for which X * w = 0. Now, note that picking v 1 = w, v 2 = 0, and λ = ±i √ d 1 − 1, we satisfy equations (4) and (5). Thus, ±i √ d 1 − 1 are eigenvalues of B, both with multiplicity n − r. The remaining 4r eigenvalues of B determined by A come from nonzero eigenvalues of A.…”
Section: Connecting the Spectra Of A And Bmentioning
confidence: 99%
“…Barrett et al [4] studied the effect of these symmetries from a group theory standpoint. The work of [5] is closest to ours: they consider spectral properties of such graphs and their implications for spectral community clustering. In particular, they show that the spectrum of what we call the 'frame' (in their words, the discrete spectrum, which is deterministic) is contained in that of the random graph.…”
Section: Application: Community Detectionmentioning
confidence: 99%
“…We derive the cavity equations [16,17] to compute the continuous part of the spectrum of the adjacency matrices in equitable graphs, as shown in [18,13]. Given an ensemble of N × N symmetric matrices the set of eigenvalues of a given adjacency matrix A is denoted by {λ A i } N i=1 .…”
Section: Spectral Theory With the Cavity Methodsmentioning
confidence: 99%
“…Between each pair of blocks the edges are drawn according to a k-regular graph, where the value of k equals the corresponding element of the connectivity matrix, then the total set of edges is given by the union of the sets for each of the m 2 regular and biregular graphs [Algorithm 1]. This ensemble has been successfully studied in the context of community detection [15] and an algorithm was found that is able to identify blocks simply by looking at the list of edges in the graph [13], exploiting the symmetry of the eigenvectors of the adjacency matrix.…”
Section: Equitable Graphsmentioning
confidence: 99%
See 1 more Smart Citation